Physical and transcriptional organization of the ribosomal RNA genes of the savannah-type Trypanosoma congolense - Urakawa, T.; Majiwa, Phelix A.O. (Springer, 2001)
Ribosomal RNA genes have been cloned from the major species of African trypanosomes. Complete nucleotide sequence composition of the small subunit (SSU) and portions of the large subunit (LSU) ribosomal RNA genes was determined for each of these trypanosome species. In contrast to the situation in Trypanosoma brucei, in savannah-type T. congolense the LSU ribosomal RNA is cleaved twice, to generate two additional prominent fragments. This leads to the different profiles observed when the rRNA molecules from these two trypanosome species are resolved in agarose gels. From the nucleotide sequences of the 18S RNA, a phylogenetic tree was derived depicting the relationships among the T. congolense complex of trypanosomes and the other species of trypanosomes.